2020
DOI: 10.1101/2020.04.14.20065730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nosocomial Infections Among Patients with COVID-19, SARS and MERS: A Rapid Review and Meta-Analysis

Abstract: Background: COVID-19, a disease caused by SARS-CoV-2 coronavirus, has now spread to most countries and regions of the world. As patients potentially infected by SARS-CoV-2 need to visit hospitals, the incidence of nosocomial infection can be expected to be high. Therefore, a comprehensive and objective understanding of nosocomial infection is needed to guide the prevention and control of the epidemic. Methods: We searched major international and Chinese databases Medicine, Web of science, Embase, Cochrane, CBM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 26 publications
2
48
2
4
Order By: Relevance
“…Public Health England (PHE) has estimated the rate of nosocomial infections to be 10-22%, 3 whereas a meta-analysis of Chinese data estimated numbers 44%. 4 Our rate of nosocomial infection exceeds PHE's estimation and is also significantly higher than Trust-wide rates within our own Trust (5.2%). Reasons for this are likely multifactorial, with many identified aspects specific to our department and patient population.…”
Section: Hospital-acquired Covid-19contrasting
confidence: 63%
“…Public Health England (PHE) has estimated the rate of nosocomial infections to be 10-22%, 3 whereas a meta-analysis of Chinese data estimated numbers 44%. 4 Our rate of nosocomial infection exceeds PHE's estimation and is also significantly higher than Trust-wide rates within our own Trust (5.2%). Reasons for this are likely multifactorial, with many identified aspects specific to our department and patient population.…”
Section: Hospital-acquired Covid-19contrasting
confidence: 63%
“…Similar scale of such accommodation for workers has not been introduced in Hong Kong, and no reported transmission has occurred in similar settings. Limitation of spread from healthcare settings in this study could be related to the effective infection control practice adopted, while extensive spread has been widely reported elsewhere [25] . Transport setting characteristics involved limited short-term contact despite the large population implicated.…”
Section: Discussionmentioning
confidence: 73%
“…The present findings differ from the results of a recent review that suggested that up to 44% of COVID-19 infections may be nosocomial. 16 However, that review was limited to case series conducted early in the outbreak in Wuhan, China, before recognition of the virus and the institution of infection control practices and PPE. In contrast, hospitals in Hong Kong cared for 42 patients with COVID-19 and reported no nosocomial transmission during the first 6 weeks after the virus was first discovered in China.…”
Section: Discussionmentioning
confidence: 99%